Resuscitating preterm infants with 100% oxygen is associated with higher oxidative stress than room air. (19th June 2015) - Tataranno, ML; Oei, JL; Perrone, S; Wright, IM; Smyth, JP; Lui, K; Tarnow‐Mordi, WO; Longini, M; Proietti, F; Negro, S; Saugstad, OD; Buonocore, G
Abstract Aim The starting fraction of inspired oxygen for preterm resuscitation is a matter of debate, and the use of room air in full‐term asphyxiated infants reduces oxidative stress. This study compared oxidative stress in preterm infants randomised for resuscitation with either 100% oxygen or room air titrated to internationally recommended levels of preductal oxygen saturations. Methods Blood was collected at birth, two and 12 hours of age from 119 infants <32 weeks of gestation randomised to resuscitation with either 100% oxygen (n = 60) or room air (n = 59). Oxidative stress markers, including advanced oxidative protein products (AOPP) and isoprostanes (IsoP), were measured with high‐performance liquid chromatography and mass spectrometry. Results Significantly higher levels of AOPP were found at 12 hours in the 100% oxygen group (p < 0.05). Increases between two‐ and 12‐hour AOPP (p = 0.004) and IsoP (p = 0.032) concentrations were significantly higher in the 100% oxygen group. Conclusion Initial resuscitation with room air versus 100% oxygen was associated with lower protein oxidation at 12 hour and a lower magnitude of increase in AOPP and IsoP levels between two and 12 hours of life. Correlations with clinical outcomes will be vital to optimise the use of oxygen in preterm resuscitation.